Con Vol
Con Vol
Con Vol
Consider the sum of two independent discrete random variables X and Y whose values are restricted to the non-negative integers. Let fX () denote the probability distribution of X and fY () denote the probability distribution of Y . The distribution of their sum Z = X + Y is given by the discrete convolution formula. Theorem Discrete Convolution Formula. The random variable Z = X + Y has probability distribution fZ () given by
z
fX (x)fY (z x)
for z = 0, 1, ... . Proof: For each z, the event [Z = z] is the union of the disjoint events [X = x and Y = z x] for x = 0, 1, ..., z. Consequently, P ( Z = z ) = fZ (z) = =
z x=0 z x=0
P (X = x and Y = z x) fX (x)fY (z x)
where the last step follows by independence. Let X1 and X2 be independent binomial random variables having the same probability of success. Their sum is again binomial. Corollary 1 Sum of Binomial Random Variables. Let X1 and X2 be independent binomial random variables where Xi has a Binomial(ni , p) distribution for i = 1, 2. Then
X1 + X2
Let X1 , X2 , ...Xk be independent binomial random variables where Xi has a Binomial(ni , p) distribution for i = 1, 2, ..., k. Then X1 + X2 + Xk has a Binomial(n1 + n2 + + nk , p) distribution.
P (X1 + X2 = z) = fZ (z) =
x=0
fX1 (x)fX2 (z x)
so
z
fZ (z) =
x=0
= pz (1 p)n1 +n2 z
x=0 y
n1 n2 )( ) x zx
Now, equating the coecients of s in the binomial expansion of both sides of (1 + s)n (1 + s)n = (1 + s)n1 +n+2 1 2 we conclude that
z
(
x=0
n + n2 n2 n1 ) ) = ( 1 )( z zx x
The case for several binomial random variables follows by induction. Remark: Note that the sample sizes add but the success probability remains the same. Corollary 2 Sum of Poisson Random Variables. Let X1 and X2 be independent Poisson random variables where Xi has a Poisson (i ) distribution for i = 1, 2. Then X1 + X2 has a Poisson distribution with 1 + 2
Let X1 , X2 , ...Xk be independent Poisson random variables where Xi has a Poisson (i ) distribution for i = 1, 2, ..., k. Then X1 + X2 + Xk has a Poisson(1 + 2 + + k ) distribution.
P (X1 + X2 = z) = fZ (z) =
x=0
fX1 (x)fX2 (z x)
so fZ (z) =
z x=0
x 1 zx 2 2 1 e e x! (z x)!
z x=0
x zx 2 1 x! (z x)!
(a + b)m =
x=0
m x mx )a b x
with m = z, a = 1 and b = 2 after multiplying and dividing by z!, to conclude that z x zx ( 1 + 2 )z 2 1 = z! x=0 x! (z x)! and the result is established. Remark: Note that the rate parameters i add.